1986
DOI: 10.1111/j.1574-6968.1986.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt requirements for membrane transport and solute retention in some moderate halophiles

Abstract: Many species of bacteria isolated from saline environments require Na+ specifically for membrane transport. Transport occurs by a Na+ symport process energized by an electrochemical gradient of Na+ ions. The gradient at neutral pH appears to be produced by a primary electrogenic extrusion of protons coupled to a secondary, outwardly directed Na+ pump, a Na+/proton antiporter. At alkaline pH Vibrio alginolyticus may also produce the gradient by an energy‐dependent primary extrusion of Na+ ions. Alteromonas halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Also, he said (p. 17) it may well be "that there are bacteria that are uniquely marine because they are able to survive and grow in the sea and we have yet to find out why." In a more positive conclusion to a different paper (MacLeod 1986), he suggested that the sodium-dependent transport processes may permit faster growth than do other types of transport processes. This ability has selective advantages when predators are present and may explain why marine bacteria often have a sodium dependency.…”
Section: Sodium Requirementmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, he said (p. 17) it may well be "that there are bacteria that are uniquely marine because they are able to survive and grow in the sea and we have yet to find out why." In a more positive conclusion to a different paper (MacLeod 1986), he suggested that the sodium-dependent transport processes may permit faster growth than do other types of transport processes. This ability has selective advantages when predators are present and may explain why marine bacteria often have a sodium dependency.…”
Section: Sodium Requirementmentioning
confidence: 95%
“…A soecology based on the physiology of microbes dium/proton antiporter maintains a downin the laboratory. This path has led to idenhill gradient of sodium into the cell tification of many of the forms present, a (MacLeod 1986). Additional studies by detailed knowledge of the physiology of MacLeod (summarized by MacLeod 1985) many forms, and from this an understandand others (Datta and MacQuillan 1987) ing of the various steps that occur in the show similar sodium dependence for a vacycles of elements and of organic matter in riety of organisms for every metabolite lakes, rivers, and oceans.…”
mentioning
confidence: 98%
“…On the other hand, the irreplaceable minimum requirement of NaCl (or similar salts) for growth also point to a specific role for NaCl (or one of its ions). Macleod (1986) has identified an osmotic function of NaCl for the retention of accumulated solutes in the moderate halophile Alteromonas haloplanktis, and in V. costicola, although sucrose was not investigated. It seems likely that different cellular functions will respond differently to ionic and non-ionic solutes in various halophiles.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of Na+-dependence in halophilic and marine bacteria is being dealt with in detail by MacLeod elsewhere in this issue [33]. Suffice it to say that in several such organisms, including V. costicola, with which we have been especially concerned, there seems to be a Na+/H + antiport and probably a symport between Na ÷ ions and a number of substrates, including a-aminoisobutyric acid (AIB), which is widely studied as an amino acid analogue.…”
Section: Studies Of Active Transportmentioning
confidence: 99%